Impact of Student Loan Debt on Stock Ownership: An Analysis Based on the Survey of Consumer Finances - Coakley, Jordan; Li, Meng (Journal of Accounting and Finance, 2020)
This paper explores the effect of student loan debt on stock ownership in young people based on the Federal Reserve’s Survey of Consumer Finances 2016. Consistent with the finding of a negative relationship between student loan debt and stock market participation using 1992-2013 data across all age groups by Batkeyev et al. (2016), our regression also shows a negative association between student loan debt and stock ownership. These results suggest that young people invest less in the stock market when they have more student loan debt.